Designing Microfluidic-Chip Filtration with Multiple Channel Networks for the Highly Efficient Sorting of Cell Particles - Chun, Myung-Suk (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Microfluidic-chip based hydrodynamic filtration is one of the passive sorting techniques that can separate cell or particle suspensions into subpopulations of different sizes. As the branch channels and side channels play an important role in maintaining particle focusing, their rational design is necessary for highly efficient sorting. A model framework involving multiple side and multiple branch channels has been developed by extending the analytical analysis of three-dimensional laminar flow in channel networks, which was previously validated by comparison with numerical simulations. Objective parameters were identified as the number of branch channels and each length of individual branches. The presence of multiple side channels causes an increase in the average fluid velocity in main and branch channels as the branch point shifts toward the end of the main channel, which differs from the behavior observed in a single side channel. The number of branches and their individual lengths decrease distinctly in the case of branch channels consisting of narrow and wide sections, which enables the compact design of a microfluidic-chip, being operated by a lower pressure drop under the same throughput. Sorting of bidisperse particles was accomplished with an optimally designed chip to verify this framework by achieving very high recovery and purity.